2021
DOI: 10.3389/fonc.2021.672586
|View full text |Cite
|
Sign up to set email alerts
|

CircKEAP1 Suppresses the Progression of Lung Adenocarcinoma via the miR-141-3p/KEAP1/NRF2 Axis

Abstract: BackgroundLung cancer is the leading cause of death from cancer, and lung adenocarcinoma (LUAD) is the most common form. Despite the great advances that has been made in the diagnosis and treatment for LUAD, the pathogenesis of LUAD remains unclear. In this study, we aimed to identify the function of circKEAP1 derived from the exon of KEAP1 in LUAD.MethodsThe expression profiles of circRNAs in LUAD tissues and adjacent non-tumor tissues were analyzed by Agilent Arraystar Human CircRNA microarray. The levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
3
0
2
Order By: Relevance
“…In dong’s study of breast cancer in vivo and in vitro, low expression of MEG3 sponge miR-141-3p affected cell proliferation performance and apoptosis, which was negatively correlated with high expression of miR-141-3p [ 31 ]. Meanwhile, circKEAP1 inhibited the progression of LUAD by targeting miR-141-3p and opened a new idea for the treatment of LUAD [ 32 ], which was consistent with our study. The previous analysis confirmed that ATP2B1-AS1 specifically binds to miR-141-3p to participate in the development of LUAD and play a regulatory role in the prognosis of patients from the aspects of cell function and biological mechanism.…”
Section: Discussionsupporting
confidence: 90%
“…In dong’s study of breast cancer in vivo and in vitro, low expression of MEG3 sponge miR-141-3p affected cell proliferation performance and apoptosis, which was negatively correlated with high expression of miR-141-3p [ 31 ]. Meanwhile, circKEAP1 inhibited the progression of LUAD by targeting miR-141-3p and opened a new idea for the treatment of LUAD [ 32 ], which was consistent with our study. The previous analysis confirmed that ATP2B1-AS1 specifically binds to miR-141-3p to participate in the development of LUAD and play a regulatory role in the prognosis of patients from the aspects of cell function and biological mechanism.…”
Section: Discussionsupporting
confidence: 90%
“…18 Interestingly, circKEAP1 has been suggested to competitively bind to microRNA (miRNA)−141-3p and relived miR-141-3p suppression for its host gene (Keap-1), thus suppressing the LUAD progression via the Nrf2/Keap-1 pathway. 19 Our mechanistical investigations revealed that circPIBF1 silencing could prevent the nuclear translocation of Nrf2. While additional rescue experiments using the pathway activator exhibited that induction of the Nrf2/Keap-1 pathway could mitigate the pro-pyroptotic effects of circPIBF1 Intriguingly, histone writer EP300 has been revealed to bind to circSOD2 promoter and trigger its promoter H3K27ac modification, which further stimulated circSOD2 expression in hepatocellular carcinoma.…”
Section: Overexpression Of Ep300 or Sod2 Impairs The Repressing Effec...mentioning
confidence: 82%
“…Noncoding RNA‐mediated regulation of NRF2 and interplay between Nrf2 and noncoding RNAs have added new layers of complexity to already intricate nature of Nrf2, while there are little clues about interplay between circRNAs and Nrf2 in cancers 18 . Interestingly, circKEAP1 has been suggested to competitively bind to microRNA (miRNA)−141‐3p and relived miR‐141‐3p suppression for its host gene (Keap‐1), thus suppressing the LUAD progression via the Nrf2/Keap‐1 pathway 19 . Our mechanistical investigations revealed that circPIBF1 silencing could prevent the nuclear translocation of Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to identify a potential therapeutic target for patients with LUAD, a type of lung cancer that accounts for ~60% of all cases and has a 5-year survival rate of <20% ( 2 , 7 ). Although significant progress has been made in the molecular targeted therapy of LUAD, particularly for those with specific mutations in EGFR, ALK, RET and ROS1 ( 3 , 24 27 ), the high heterogeneity and complex molecular patterns of LUAD limit the applicability of these targeted therapies, thus leaving a number of patients without effective treatment options ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is a leading cause of cancer-associated mortality worldwide, and is frequently associated with a poor prognosis due to being diagnosed at an advanced stage ( 1 ). The most prevalent histological subtype of lung cancer is lung adenocarcinoma (LUAD), which accounts for ~60% of cases globally ( 2 ). In recent years, notable progress has been made in LUAD treatment with the use of molecular targeted therapies ( 3 ).…”
Section: Introductionmentioning
confidence: 99%